Model Procont Games: Inovasi Pembelajaran IPAS untuk Meningkatkan Keterampilan Berpikir Kritis dan Kolaborasi Murid Sekolah Dasar - Nidaul Husna; Maimunah (Mataram University, 2026)
This study was motivated by the low levels of student engagement, critical thinking skills, collaboration skills, and student learning outcomes in the IPAS subject. This indicates that the learning model previously used has not been able to create an active learning process or effectively encourage students to think critically and collaborate. This study aims to describe teacher activities and analyze student activities, critical thinking skills, collaboration skills, and student learning outcomes using the Procont Games model. The Procont Games model is a combination of three learning approaches: Problem-Based Learning, Contextual Teaching and Learning, and Team Games Tournament. This study employed a qualitative approach using Classroom Action Research (CAR), conducted over four sessions. The research subjects were fourth-grade students at SDN Benua Anyar 8 in Banjarmasin during the 2025/2026 school year, consisting of 21 students 13 boys and 8 girls. Data collection techniques included observation sheets and written tests, while data analysis was conducted using percentages and classical success indicators. The results of the study show that teacher activity, student activity, critical thinking skills, collaboration skills, and overall learning outcomes reached 100%. It can be concluded that the use of the Procont Games model successfully improved teacher activity, student activity, critical thinking skills, collaboration skills, and learning outcomes in elementary school students’ IPAS (Integrated Natural Sciences) lessons.